2014
DOI: 10.3390/buildings4010027
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Impact of Wind Gust Frequency on Air Exchanges in Buildings with Variable External and Internal Leakages

Abstract: Wind-driven air infiltration has been recognized among the major reasons for energy loss in buildings, and the impact to energy efficiency under steady conditions has been reported and issued as part of many building codes. The nearly zero-energy building demand makes uncontrolled leakage paths even more undesired and creates the need for further investigation of their behavior under unsteady wind conditions. The present numerical study examines the role of wind gustiness on instantaneous infiltration rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This different finding perhaps can be explained by the fact that steady wind used in the theoretical study is more stable than that achieved in real case scenarios, where the wind may fluctuate in a range due to various environmental and terrain factors and therefore exhibit a dynamic behaviour. This dynamic nature of wind, also termed as 'wind fluctuation frequency' or 'wind gustiness', was investigated by Kraniotis [35,36,37] in a number of numerical and experimental studies where its impact on the infiltration rate was studied. The results showed that higher wind fluctuation frequency potentially led to greater air change rate and the estimation uncertainty also became greater.…”
Section: Introductionmentioning
confidence: 99%
“…This different finding perhaps can be explained by the fact that steady wind used in the theoretical study is more stable than that achieved in real case scenarios, where the wind may fluctuate in a range due to various environmental and terrain factors and therefore exhibit a dynamic behaviour. This dynamic nature of wind, also termed as 'wind fluctuation frequency' or 'wind gustiness', was investigated by Kraniotis [35,36,37] in a number of numerical and experimental studies where its impact on the infiltration rate was studied. The results showed that higher wind fluctuation frequency potentially led to greater air change rate and the estimation uncertainty also became greater.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic action of the wind [32][33][34][35][36][37][38][39][40] often determines the largest share of air exchange (depending on the specifics of climate) of the building and subsequently fuels preoccupations for stochastic, harmonic, and time-series analysis. [41][42][43][44][45][46] The timebased measurements of air leakage provide an opportune and reliable source of inspiration concerning its mathematical apparatus as they deliver the best evaluation at low-pressure variations by revealing the induced harmonics of the pressure signal through Fourier analysis.…”
Section: Previous Approaches To Air Exchange In Transient Conditionsmentioning
confidence: 99%
“…Studies suggest that the fluctuating wind pressures on buildings can have a significant impact on the air infiltration of buildings, with high gust incidents increasing significantly the total air changes [19][20][21][22]. In addition, the probabilistic and statistical characteristics of the wind pressure coefficients have been described and probability distribution functions (pdf) can be used to describe their fluctuating nature and capture their peak values [23].…”
Section: Introductionmentioning
confidence: 99%
“…At the Middle West measuring position, the negative values make up 8% of the total measured wind pressure coefficients.The wind velocities measured during the measuring period were used. Only wind directions within the angle range [−22.5°,22.5°] that correspond to the North wind direction were selected.…”
mentioning
confidence: 99%